Identification and Measurement of Multidimensional Relative Poverty of Chinese Rural Adults Considering Climate Factors - Hou, Xiaoyuan; Wu, Haitao; Wang, Wei (Frontiers in Environmental Science, 2022)
The climate conditions in different regions of China are different, resulting in uneven climate resources owned by residents. It is important to design a comprehensive evaluation method to measure the multidimensional relative poverty (MRP) status and differences in rural areas considering climate factors from the micro-level. With adults as the research object, imitating multidimensional poverty index (MPI) and other indexes, and referring to the relative poverty lines in Britain, Australia, and other countries, this study considers the housing sunshine level and air quality of living environment, which can reflect the superposition of economy and climate, in the dimension of human settlements environment, and establishes an indicator system of MRP in rural China. Using the Chinese General Social Survey data in 2018 and the A-F method to measure the indicator poverty rate, multidimensional relative poverty index (MRPI), and indicator contribution rate, this study evaluates the MRP in rural China including climate factors. The results show that the poverty rate of sunshine level and air quality indicator in North China is the highest in China, and the MRPI is the lowest. In North China, the sunshine level and air quality indicator poverty rate are 17.47% and 53.01%, respectively. MRPI under K=1 standard is 0.1182. It shows that the indicator system can identify the typical phenomenon that highly industrialized economic development may negatively affect the environment. MRP alleviation should focus on coordinated governance of the economy, education, health and the human settlements, we should establish a climate emergency plan for joint prevention and control with the meteorological department, set afforestation protection area, set climate-related building standards such as sunshine times of rural houses, and improve and upgrade the energy use in rural areas to achieve the harmonious development of the society, economy and environment and the high-quality life pursued by rural residents.